Banks and non-banks stressed: Liquidity shocks and the mitigating role of insurance companies - Matthias Sydow; Gábor Fukker; Tomasz Dubiel-Teleszynski; Fabio Franch; Sébastien Gallet; Helmut Gründl; Stelios Kotronis; Debora Miccio; Michela Pellegrino; Sebastian Schlütter; Matteo Sottocornola (European Central Bank (ECB), 2024)
This paper documents the extension of the system-wide stress testing framework of the ECB with the insurance sector for a more thorough assessment of risks to financial stability. The special nature of insurers is captured by the modelling of the liability side and its loss absorbing capacity of technical provisions as the main novel feature of the model. Leveraging on highly granular data and information on bilateral exposures, we assess the impact of liquidity and solvency shocks and demonstrate how a combined endogenous reactions of banks, investment funds and insurance companies can further amplify losses in the financial system. The chosen hypothetical scenario and subsequent simulation results show that insurers' ability to transfer losses to policyholders reduces losses for the entire financial sector. Furthermore, beyond a certain threshold, insurance companies play a crucial role in mitigating both direct and indirect contagion.
Keywords: D85; G01; G21; G23; L14; 330; Financial stability; stress test; interconnectedness; insurance companies; fire sales; contagion